Investigation of In Vitro Apocarotenoid Expression in Perianth of Saffron (Crocus sativus L.) Under Different Soil EC - Mandana Mirbakhsh; Zahra Zahed; Sepideh Mashayekhi; Monire Jafari (Politeknik Negeri Jember, 2023)
Crocus sativus is a triploid sterile plant with red stigmas belonging to family of Iridaceae, and sub family Crocoideae. Crocin, picrocrocin, and safranal are three major carotenoid derivatives that are responsible for color, taste and specific aroma of Crocus. Saffron flowers are harvested manually and used as spice, dye or medicinal applications. The natural propagation rate of most geophytes including saffron is relatively low. An in vitro multiplication technique like micropropagation has been used for the propagation of saffron. To understand the efficiency of this alternative and study the molecular basis of apocarotenoid biosynthesis/accumulation, the RT-PCR method was performed on perianth explants that were cultured on MS medium to observe the level of expression of zeaxanthin cleavage dioxygenase (CsZCD) gene during stigma development, and also the impact of soil EC on its expression. The present study was conducted at Plant molecular and physiology Lab, Alzahra University, Tehran, Iran during 2011-2013. Stigma-like structures (SLSs) on calli were collected from immature perianth explants from floral buds of corms that were collected from Ghaen city, and compared to (Torbat-e Haidariye, Mardabad and Shahroud cities) for investigating the impact of different soil EC on CsZCD expression. The results indicated that CsZCD gene was highly expressed in fully developed red SLSs in perianth of cultured samples of Shahroud with the highest salinity. In this research, a close relationship between soil EC and second metabolites regulation is studied. Overall, these results will pave the way for understanding the molecular basis of apocarotenoid biosynthesis and other aspects of stigma development in C. sativus.